2020
DOI: 10.3390/rs12061050
|View full text |Cite
|
Sign up to set email alerts
|

BRRNet: A Fully Convolutional Neural Network for Automatic Building Extraction From High-Resolution Remote Sensing Images

Abstract: Building extraction from high-resolution remote sensing images is of great significance in urban planning, population statistics, and economic forecast. However, automatic building extraction from high-resolution remote sensing images remains challenging. On the one hand, the extraction results of buildings are partially missing and incomplete due to the variation of hue and texture within a building, especially when the building size is large. On the other hand, the building footprint extraction of buildings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(114 citation statements)
references
References 36 publications
1
113
0
Order By: Relevance
“…As shown in Figure 2, compared with the ordinary convolution layer, the atrous convolution can effectively expand the receptive field of feature extraction, retaining the feature size and reducing the loss of spatial information of features without increasing parameters. It has been proved to be an effective feature extraction approach [50]. We use multiple parallel atrous convolution branches in the Resblock module of the network to obtain the global characteristics of the road surface and road centerline in remote sensing images.…”
Section: Resblockmentioning
confidence: 99%
“…As shown in Figure 2, compared with the ordinary convolution layer, the atrous convolution can effectively expand the receptive field of feature extraction, retaining the feature size and reducing the loss of spatial information of features without increasing parameters. It has been proved to be an effective feature extraction approach [50]. We use multiple parallel atrous convolution branches in the Resblock module of the network to obtain the global characteristics of the road surface and road centerline in remote sensing images.…”
Section: Resblockmentioning
confidence: 99%
“…To validate the generalization of the proposed method on imagery with a different spatial resolution, we conducted experiments on the Massachusetts dataset to compare the performance of our and related works. BRRNet [62] designed a prediction module based on the encoder-decoder structure with a residual refinement module for accurate boundary extraction. The results showed that our method outperformed the classical semantic segmentation methods and the most recent building extraction methods, as shown in Table 3.…”
Section: Experiments On the Massachusetts Datasetmentioning
confidence: 99%
“…Specifically, the same class of remote sensing images might have a diverse appearance [29]. Numerous studies have shown superior performances to the traditional handcrafted features in CBRSIR, based on the great success of the convolutional neural network (CNN) in representing high-level visual features of images [31][32][33][34][35][36][37][38]. Similarly, numerous studies are underway to increase retrieval accuracy by extracting more discriminative features of the images, considering the small and intricate targets contained in the remote sensing images.…”
Section: A Content-based Remote Sensing Image Retrieval (Cbrsir)mentioning
confidence: 99%